ANALISIS PENGGUNAAN INSENTIF PPH FINAL UMKM SEBAGAI SALAH SATU PROGRAM PEMULIHAN EKONOMI NASIONAL TERHADAP PENERIMAAN PAJAK DI KPP PRATAMA PANGKAL PINANG - Ade Emilya Sepa; Safrizal Safrizal (Jurusan Akuntansi FEB UNTAN, 2023)
On May 31, 2020 the government issued a policy as a form of effort as well as a legal umbrella program aimed at overcoming national economic and health problems as a result of the corona virus, namely the Covid-19 Handling Program and National Economic Recovery. One of these programs is to provide support for small and medium enterprises to continue to run their business as a step that can support the movement of the national economy. This support is carried out by providing tax incentives in the form of Final PPh borne by the government. The tax that is borne is the tax that is imposed based on Government Regulation Number 23 of 2018. The incentive was initially given during the April 2020 Tax Period until the September 2020 Tax Period, then the government issued apolicy again so that the incentive could be used until December 2021. Not until there in 2022 the government again issued a policy that regulates the granting of tax-free facilities to individual Final Income Tax having accumulated turnover in one tax year not exceeding IDR 500,000,000.00. This facility is expected to be used optimally by business actors and can ease the burden by increasing their income. However, in reality the use of this incentive has not been implemented by all MSME actors, including taxpayers in the Pangkal Pinang KPP Pratama work area. And this is directly proportional to the contribution of the final PPh tax payment borne by the government towards the realization of KPP revenues.